1997
DOI: 10.2535/ofaj1936.74.2-3_81
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Magnesium on the Fine Structure of the Golden Hamster Parathyroid Gland in Vivo and in Vitro

Abstract: Summary:We examined the effect of magnesium (Mg) on the fine structure of the golden hamster parathyroid gland in vivo and in vitro. In the in vivo study, the principal changes in the parathyroid glands 10 and 30 min, and 1 hr after Mg injection showed a significant decrease in the area of the Golgi apparatus and cisternae of the rough endoplasmic reticulum compared with those of the control animals. The serum calcium level in the experimental animals 30 min and 1 hr after the injection was significantly low c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1997
1997
1997
1997

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…It is biochemically or ultrastructurally reported that Mg decreases the activity of the PTH (Altenahr and Leonhardt, 1972;Cholst et aL, 1984;Suzuki et aL, 1986;Utsumi et aL, 1997). In the PTG of the 1.2G group the rER had significantly increased cornpared with that of the control group.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…It is biochemically or ultrastructurally reported that Mg decreases the activity of the PTH (Altenahr and Leonhardt, 1972;Cholst et aL, 1984;Suzuki et aL, 1986;Utsumi et aL, 1997). In the PTG of the 1.2G group the rER had significantly increased cornpared with that of the control group.…”
Section: Discussionmentioning
confidence: 92%
“…On the other hand, it is well known in the biochemical or morphological study that magnesium (Mg) plays an important role in the regulation of parathyroid hormone secretion as well as calcium (Altenahr and Leonhardt, 1972;Cho1st et al , 1984;Suzuki et aL, 1986;Utsumi et aL, 1997).…”
mentioning
confidence: 99%